More Than Words: The Use of Video in Ethnographic Research With People With Intellectual Disabilities. (June 2019) - Kaley, Alexandra; Hatton, Chris; Milligan, Christine
There is a tendency to exclude people with intellectual disabilities from participating in research about their own lives. While the use of participatory research approaches is increasing, the methods used for engaging people with intellectual disabilities in research are generally limited to interviews and focus groups. Yet a focus on the spoken or written word can present a challenge for those who may prefer to use alternative forms of communication. The purpose of this article is to share the methodological insights gained from a visual ethnographic study that sought to explore the experiences of people with intellectual disabilities engaged in nature based (or "green care") therapeutic interventions for health and well-being. If used within carefully negotiated relationships, we suggest that video can be an empowering visual medium for doing research that can help to elicit the experiences of people with intellectual disabilities firsthand, without having to rely on the views and perspectives of other people.